Pembelajaran Problem Solving Modifikasi untuk Meningkatkan Kemampuan Pemahaman Konsep Matematis Siswa SMP - Fahrudin, Fahrudin; Netriwati, Netriwati; Putra, Rizki Wahyu Yunian (Desimal: Jurnal Matematika, 2018)
The purpose of this study is to determine the improvement of the ability to understand mathematical concepts with problem-solving learning modification better than the ability to understand mathematical concepts with conventional learning. This research is a quantitative research type of quasi-experiment. Hypothesis test used in this research is t-test. The result of research indicates that the improvement of students' mathematical concept comprehension ability using problem-solving learning modification is better than the ability to understand mathematical concept using conventional learning.